THE CONCEPT AND CONTEXTUALIZATION OF THE DIRECTION OF THE STATE AS AN INSTRUMENT OF DEVELOPMENT - Ahmad Ahmad (Universitas Muhammadiyah Tangerang, 2022)
The concept and contextualization of the state policy before and after the amendment to the 1945 Constitution as a pattern of national development planning as an effort to realize the goals of the state as stated in the Pancasila preamble and the Preamble to the 1945 Constitution attached to the position of the People's Consultative Assembly is the main issue in this research. The research method used is doctrinal legal research with a descriptive analysis approach. The results showed that the concept of state policy before the amendment of the 1945 Constitution was attached to the position of the People's Consultative Assembly as the highest state institution by placing the President who was elected by and also at the same time the mandate of the People's Consultative Assembly so that he is responsible to the People's Consultative Assembly. The contextualization of the state policy before and after the amendment to the 1945 Constitution has given rise to the discourse of the fifth amendment by giving the People's Consultative Assembly the authority to determine the state's direction as a pattern of development planning, not only on the campaign promises of the elected President as the basis for development planning. Keywords: Concept, Contextualization, Development Planning, State Policy